Accelerated Shelf Life Test (Aslt) Method with Arrhenius Approach for Shelf Life Estimation of Sugar Palm Fruit Jam With Addition of Asian Melastome (Melastoma malabathricum, l.) on Jar Packaging and Pouch - Anna Anggraini (Green Engineering Society, 2019)
Abstract. Base on previous studies showing that sugar palm fruit can be made as jam with the addition of Asian melastome fruit as a natural coloring. This sugar palm fruit jam product is packaged with jar and pouch packaging. shelf Life information for this product is unknown. The purpose of this study is to determine the rate of change in quality, critical parameters, and estimate the shelf life of sugar palm fruit jam with Arrhenius Model which is simulated at three storage temperature conditions (28⁰C, 38⁰C, and 48⁰C). Parameters observed during the storage process are water content, water activity (aw), pH, color (L), anthocyanin, and antioxidant activity (IC50). The results showed that the smallest activation energy value was used to determine product shelf life, it is color parameters (L) (first order reaction) with linear regression y = -4715.x + 9,787 on jar bottle packaging and y = -2021.x + 1,387 on packaging pouch. The age of storing sugar palm fruit jam with jar bottles is 93 days at 28⁰C and on the packaging pouch for 40 days at 28⁰C.